1986
DOI: 10.1073/pnas.83.23.9216
|View full text |Cite
|
Sign up to set email alerts
|

Substance P receptors in primary cultures of cortical astrocytes from the mouse.

Abstract: Binding sites for substance P were labeled on intact cortical glial cells from newborn mice in primary culture using 1251-labeled Bolton-Hunter-labeled substance P. Maximal specific binding (95% of total binding) was reached after 2-3 weeks in culture. The binding was saturable, reversible, and temperature dependent. Scatchard and Hill analysis revealed a single population of noninteracting high-affinity binding sites (Kd, 0.33 nM; B., 14.4 fmol per dish). Competition studies made with tachykinins and substanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
26
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 79 publications
(31 citation statements)
references
References 28 publications
(21 reference statements)
5
26
0
Order By: Relevance
“…In the present report, we have demonstrated that after optic nerve transection, substance P binding sites are expressed in high concentrations by cells comprising the glial scar in the optic nerve and optic tract. These data are consistent with previous in vitro studies that demonstrated that substance P receptors are present in 2-to 3-week-old primary cultures of cortical astrocytes from newborn mice and that addition of substance P to these astrocyte cultures stimulates phosphatidylinositol turnover (16). Substance P has also been shown to stimulate the cyclooxygenase pathway of arachidonic acid metabolism in 2-to 3-week-old cultures of rat astrocytes and to evoke the formation of prostaglandin E and thromboxane B2 in a dose-dependent manner (13).…”
Section: Resultssupporting
confidence: 82%
“…In the present report, we have demonstrated that after optic nerve transection, substance P binding sites are expressed in high concentrations by cells comprising the glial scar in the optic nerve and optic tract. These data are consistent with previous in vitro studies that demonstrated that substance P receptors are present in 2-to 3-week-old primary cultures of cortical astrocytes from newborn mice and that addition of substance P to these astrocyte cultures stimulates phosphatidylinositol turnover (16). Substance P has also been shown to stimulate the cyclooxygenase pathway of arachidonic acid metabolism in 2-to 3-week-old cultures of rat astrocytes and to evoke the formation of prostaglandin E and thromboxane B2 in a dose-dependent manner (13).…”
Section: Resultssupporting
confidence: 82%
“…In contrast to its absence of effect on these peripheral targets, SP has been confirmed in this study, in a cellular model representative of astrocytes of the central nervous system, as a very effective inducing or potentiating agent of this type of mediators. Functional SP receptors have been identified in mouse and rat primary astrocytes [30,31] and enhanced secretion of inflammatory cytokines has been demonstrated upon SP stimulation of these cells [32,33]. This indicates that the pro-inflammatory effect of SP observed on astrocytoma cell lines can be extended to normal primary astrocytes.…”
Section: Discussio•mentioning
confidence: 76%
“…Evidence exists that amino acids are released by high-K+ solution in a Ca*+-independent manner (Drejer et al, 1982(Drejer et al, , 1983 and that astrocytes may be intimately involved in neurotransmission processes, amino acid uptake (Hertz and Schousboe, 1986;Hijsli et al, 1986) and they possess receptors for amino acid transmitters (Glu, Asp, GABA) and peptides (Bowman and Kimelberg, 1984;Kettermann and Schachner, 1985;Hamprecht, 1986;Torrens et al, 1986). Binding sites for SP were detected on glial cells of the spinal cord and SP enhances accummulation of labeled inositol phosphates in cultures of cortical glial cells from the mouse (Torrens et al, 1986). In addition, synthetic human calcitonin raises intracellullar concentration of cyclic AMP in rat astroglia cells (Hamprecht, 1986).…”
Section: Aspmentioning
confidence: 99%